The Effects of Chilling Temperature of Bone-in Fully-Cooked Hams on Microbial Growth and Shelf Life - Chad Carr; Larry Eubanks (EDIS)
AN206, a 4-page fact sheet by C. Chad Carr and Larry Eubanks, reports the results of a study to determine the effect of not meeting the USDA’s suggested standard for chilling on the microbial growth and retail acceptability of bone-in, fully-cooked hams. Includes references. Published by the UF Department of Animal Science, October 2008.